Australians' knowledge and perceptions of direct‐to‐consumer personal genome testing. Issue 1 (January 2014) - Savard, J.; Mooney‐Somers, J.; Newson, A. J.; Kerridge, I.
Abstract Background As direct‐to‐consumer personal genome testing (DTC‐PGT) is increasingly available in Australia, knowledge of Australians' perceptions and attitudes towards this technology is needed in order to assess the (potential) impact it might have on the Australian public and healthcare system. Aims To explore the knowledge and perceptions of DTC‐PGT in an Australian sample. Methods An online survey asking about knowledge and perceptions of DTC‐PGT, undertaken between October 2011 and April 2012, of 270 Australian residents. Results were analysed using SAS. Results Our study found limited consumer knowledge of, and interest in, pursuing DTC‐PGT in Australia. Ninety‐three per cent of respondents correctly identified DTC‐PGT as available to consumers directly, but only 40% correctly identified its availability in Australia. When asked about the content and value of the information DTC‐PGT provides, the majority of respondents indentified that DTC‐PGT could provide information about one's health and/or ancestry (82% and 74%). Additionally, respondents indicated they believed this information to be equally important as non‐genetic information about one's ancestry and health. Conclusion While a minority of respondents expressed an intention to pursue DTC‐PGT (27%), the majority of respondents, irrespective of whether they wished to pursue it or not, believed that genetic information was as important as non‐genetic information in regards to their health and their ancestry. The value ascribed to genetic information suggests that genetics plays a role in people's lives, and that further qualitative research could explore the ways in which people might use and understand the genetic information provided by DTC‐PGT.